Hydration breaking and chemical ordering in a levitated NaCl solution droplet beyond the metastable zone width limit: evidence for the early stage of two-step nucleation. Issue 1 (16th December 2020) - Hwang, Hyerim; Cho, Yong Chan; Lee, Sooheyong; Lee, Yun-Hee; Kim, Seongheun; Kim, Yongjae; Jo, Wonhyuk; Duchstein, Patrick; Zahn, Dirk; Lee, Geun Woo
Abstract : This work provides evidence for two-step nucleation in highly supersaturated bulk NaCl solution, using electrostatic levitation combined with Raman/X-ray scatterings. Abstract : For over two decades, NaCl nucleation from a supersaturated aqueous solution has been predicted to occur via a two-step nucleation (TSN) mechanism, i.e., two sequential events, the formation of locally dense liquid regions followed by structural ordering. However, the formation of dense liquid regions in the very early stage of TSN has never been experimentally observed. By using a state-of-the-art technique, a combination of electrostatic levitation (ESL) and in situ synchrotron X-ray and Raman scatterings, we find experimental evidence that indicates the formation of dense liquid regions in NaCl bulk solution at an unprecedentedly high level of supersaturation ( S = 2.31). As supersaturation increases, evolution of ion clusters leads to chemical ordering, but no topological ordering, which is a precursor for forming the dense disordered regions of ion clusters at the early stage of TSN. Moreover, as the ion clusters proceed to evolve under highly supersaturated conditions, we observe the breakage of the water hydration structure indicating the stability limit of the dense liquid regions, and thus leading to nucleation. The evolution of solute clusters and breakage of hydration in highly supersaturated NaCl bulk solution will provide new insights into the detailed mechanism of TSN for many other aqueous solutions.